How to define and build an effective cyber threat intelligence capability - Dalziel, Henry (Waltham, Massachusetts : Elsevier, 2015)
One of the most important concepts in the world of information security today is defining and building an effective cyber threat intelligence capability. Covers the keys to successful implementation and discusses who are the right vendors, partners, or employees to build, staff, and run your cyber threat intelligence program
1. A problem well-defined is half-solved -- 2. Defining business objectives or "start with why" -- 3. Common objectives of a threat intelligence program -- 4. Translating objectives into needs. "Why drives what" -- 5. How technology models operationalize threat data -- 6. Who: given why, what, and how, how you can ask where to get it
Keywords: Computer crimes -- United States -- Prevention; Computer networks -- Security measures -- United States; Cyber intelligence (Computer security) -- United States; Cyberterrorism -- United States -- Prevention; National security -- United States